2019
DOI: 10.5944/educxx1.22620
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers volunteering in pre-service programmes in successful schools: Contributing to their successful training

Abstract: Following recent literature, the field of teacher education is considered as key factor in promoting school success. In this regard, this study is dedicated to clarifying which type of education is most effective to train successful teachers so that they can properly face the challenges of modern societies. This article contributes to this ongoing debate by providing the selfreported benefits among student teachers of the Rovira i Virgili University who have served as volunteers in Learning Communities where d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…In line with previous studies [6,8], this study suggests that students, before and after participating in the ECA, perceive that interacting with other students and with people at risk of social exclusion can help them improve their academic and professional practices. Thus, on the one hand, they consider that it can serve to complement the theoretical knowledge they have acquired during the degree and give to that knowledge a more practical and social sense [3]. On the other hand, they believe that it can help them to acquire professional experience and develop skills, such as cooperation and initiative that will favor future professional performance [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies [6,8], this study suggests that students, before and after participating in the ECA, perceive that interacting with other students and with people at risk of social exclusion can help them improve their academic and professional practices. Thus, on the one hand, they consider that it can serve to complement the theoretical knowledge they have acquired during the degree and give to that knowledge a more practical and social sense [3]. On the other hand, they believe that it can help them to acquire professional experience and develop skills, such as cooperation and initiative that will favor future professional performance [8].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, one of the biggest challenges in higher education is to foster personal attitudes among students that will enable them to move toward more equitable, just, and sustainable societies. In this 2 of 17 context, a growing body of literature has studied how ECAs contribute to this goal [3][4][5]. Furthermore, research in this field has indicated the impact of ECA in terms of achieving higher levels of academic performance [6], having more successful development during university life [7], improving later employment adaptation [8], and obtaining more significant social and psychological resources that aid the students' mental well-being [9].…”
Section: Introductionmentioning
confidence: 99%
“…Por ende, se requieren metodologías de verdaderos programas de formación que, en palabras de (RÍOS GONZALEZ et al, 2019), permitan reducir los niveles de desigualdad educativa mediante teorías y prácticas eficaces, como lo sugiere (RODRÍGUEZ-FERNÁNDEZ et al, 2018).…”
Section: Referentes Teóricosunclassified